1977
DOI: 10.1083/jcb.75.3.712
|View full text |Cite
|
Sign up to set email alerts
|

Role of nerve growth factor in the development of rat sympathetic neurons in vitro. III. Effect on acetylcholine production.

Abstract: The effect of nerve growth factor (NGF) on the development of cholinergic sympathetic neurons was studied in cultures grown either on monolayers of dissociated rat heart cells or in medium conditioned by them. In the presence of rat heart cells the absolute requirement of neurons for exogenous NGF was partially spared. The ability of heart cells to support neuronal survival was due at least in part to production of a diffusible NGF-like substance into the medium. Although some neurons survived on the heart cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Patterson and Chun first showed that neurokine signaling through LIFR regulates cholinergic differentiation in sympathetic neurons (Chun & Patterson, 1977). Subsequent investigation proved that LIFR plays a role in the differentiation of other neuronal populations including adrenergic and dopaminergic neuronal populations (Fan & Katz, 1993; Lewis et al, 1994).…”
Section: The Role Of Lifr In Nervous System Developmentmentioning
confidence: 99%
“…Patterson and Chun first showed that neurokine signaling through LIFR regulates cholinergic differentiation in sympathetic neurons (Chun & Patterson, 1977). Subsequent investigation proved that LIFR plays a role in the differentiation of other neuronal populations including adrenergic and dopaminergic neuronal populations (Fan & Katz, 1993; Lewis et al, 1994).…”
Section: The Role Of Lifr In Nervous System Developmentmentioning
confidence: 99%
“…More recently, we have investigated the biophysics of neuro‐cardiac signalling, aiming to address whether the neuronal effects on the heart were the result, in accordance with the archetypal description of cardiac physiology, of the unabridged propagation of sympathetic neurotransmitters throughout the myocardium, or whether neuro‐cardiac communication was confined to specific junctional sites, similar to those involved in skeletal muscle contraction (Hall & Sanes, ; Homan & Meriney, ). This latter hypothesis arose from the results of several previous studies obtained in vitro (Chun & Patterson, ; Shcherbakova et al ., ; Oh et al ., ) and ex vivo (Fukuda et al ., ), suggesting that specific sympathetic synapses may exist in the heart. By applying SN optogenetics, we demonstrated in vivo that neurotransmission underlying the rapid and efficient chronotropic effect of SN activation depended on the local release of NE at the intercellular contact site, with features typical of synaptic transmission (Prando et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that nerve growth factor (NGF) plays a role in the establishment of appropriate neuron-target connections in the developing sympathetic nervous system. NGF is essential for the survival of sympathetic neurons (1-5) and causes dose-dependent increases in neuronal growth (3) and differentiation (3,5). There is evidence of its presence in sympathetic target tissues [e.g., salivary gland (6) and iris (7)] and it is transported retrograde by sympathetic axons to sympathetic ganglia (8,9).…”
mentioning
confidence: 99%